Особливості технології виробництва сапфіра - Стаднік, Д. В. (ХНУРЕ, 2021)
The report considers the main technologies of sapphire production. A review of methods for obtaining leucosapphire by technologies based on Czochralski's methods; Stepanova; Verneil; vertically directed crystallization; Bridgman-Stockbarger; Kiropoulos; zone melting; horizontally directed crystallization.
Keywords: виробництво сапфіра